Assessing risk factors for SARS-CoV-2 infection in patients presenting with symptoms in Shanghai, China: a multicentre, observational cohort study. Issue 6 (June 2020) - Mao, Bei; Liu, Yang; Chai, Yan-Hua; Jin, Xiao-Yan; Lu, Hai-Wen; Yang, Jia-Wei; Gao, Xi-Wen; Song, Xiao-Lian; Bao, Hong; Wang, An; Gu, Wen-Chao; Zhao, Lei; et al.
Summary: Background: The outbreak of COVID-19 has led to international concern. We aimed to establish an effective screening strategy in Shanghai, China, to aid early identification of patients with COVID-19. Methods: We did a multicentre, observational cohort study in fever clinics of 25 hospitals in 16 districts of Shanghai. All patients visiting the clinics within the study period were included. A strategy for COVID-19 screening was presented and then suspected cases were monitored and analysed until they were confirmed as cases or excluded. Logistic regression was used to determine the risk factors of COVID-19. Findings: We enrolled patients visiting fever clinics from Jan 17 to Feb 16, 2020. Among 53 617 patients visiting fever clinics, 1004 (1·9%) were considered as suspected cases, with 188 (0·4% of all patients, 18·7% of suspected cases) eventually diagnosed as confirmed cases. 154 patients with missing data were excluded from the analysis. Exposure history (odds ratio [OR] 4·16, 95% CI 2·74–6·33; p<0·0001), fatigue (OR 1·56, 1·01–2·41; p=0·043), white blood cell count less than 4 × 10 9 per L (OR 2·44, 1·28–4·64; p=0·0066), lymphocyte count less than 0·8 × 10 9 per L (OR 1·82, 1·00–3·31; p=0·049), ground glass opacity (OR 1·95, 1·32–2·89; p=0·0009), and having both lungs affected (OR 1·54, 1·04–2·28; p=0·032) were independent risk factors for confirmed COVID-19. Interpretation: The screening strategy was effective for confirming or excluding COVID-19 during the spread of this contagious disease. Relevant independent risk factors identified in this study might be helpful for early recognition of the disease. Funding: National Natural Science Foundation of China.